Castes in the Neotropical Social Wasp Leipomeles dorsata (Fabricius) (Hymenoptera: Vespidae): a Window for Workers Achieving a New Status in the Colony - Noll, Fernando Barbosa [UNESP]; Gomes, Bruno [UNESP]; Lima, Alexandre C. O.; Mateus, Sidnei; Wenzel, John W. (Entomological Soc Brasil, 2010)
Morphometric studies performed in several species of Neotropical social wasps from the tribe Epiponini showed that in some species there are marked differences between castes, while other species present highly distinct castes with differences only in ovarian development. This work analyzed females from six colonies of the social wasp Leipomeles. dorsata (Fabricius) in which queens (egglayers) and workers showed differences in ovarian development and coloration. We propose that wasps with developed ovaries (egglayers) and coloration similar to those of workers are possibly intermediates that obtained the status of queens in the colony.
Keywords: Epiponini; Caste difference; multivariate analysis